Energy efficiency: A proposal - Pendić Zoran R.; Jakovljević Bojana B.; Pastuović Nikola N.; Marković Željko M. (Tehnika, 2015)
Increase of energy efficiency in Serbia is one of the priority tasks. Sector of electric lighting offers great opportunities for increasing energy efficiency due to the rapid development of LED technology. Nowadays LED lighting is still expensive and have relatively little application in the domain of electric lighting. However, it is anticipated that LED products would soon greatly transform the electric lighting market. In recent years, LED technology has significantly improved, and constantly evolving. It is expected that advanced and future LED bulbs / lamps to be getting cheaper and with a better technical characteristics and that they will soon be dominant on the lighting market. Serbia must prepare for the LED future, creating appropriate legislation and promotion of appropriate incentive measures.